Spindle Cell Rhabdomyoscarcoma of the Tongue - A Rare Entity - Khadim, MT; Asif, A; Ali, Z; Jamal, S; Ahmad, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 27-28 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6783